A Case of Giant Basal Cell Carcinoma of the Ear Complicated by Primary Cutaneous Aspergillosis - Yao Y; Li T; Huang Y; Cheng H (Clinical, Cosmetic and Investigational Dermatology, 2022)
Yabo Yao, Tianhao Li, Yuanen Huang, Hongbin Cheng Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of ChinaCorrespondence: Hongbin Cheng, Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39, Shi-er-qiao Road, Jinniu District, Chengdu, People’s Republic of China, Email chenghongbin@cdutcm.edu.cnAbstract: A 78-year-old female patient with right ear agenesis presented with a skin manifestation of approximately 7 cm × 8 cm deep-invasive ulcer with well-defined borders and a small amount of yellow purulent discharge visible at the base, surrounded by pearl-like margins in a dyke-like elevation, covered with a small amount of necrotic tissue and black crust. The disease lasted for more than 20 years and was diagnosed as giant basal cell carcinoma complicated by primary cutaneous aspergillosis after two histopathological examinations of the skin lesions. There are similarities in the clinical manifestations of these two diseases, which need to be differentiated, and the simultaneous complications are infrequent. It has not been reported.Keywords: giant basal cell carcinoma, primary, cutaneous aspergillosis